HABITATION OF STAD TYPE COOPERATIVE LEARNING MODEL THROUGH PJBL APPROACH TOWARDS THE QUALITY OF MATHEMATICS LEARNING IN MUHAMMADYAH 1 SURAKARTA SCHOOL GRADE IV - Deska Sofiana Wahyu; Harun Joko Prayitno (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2026)
This study aims to analyze the improvement in the quality of mathematics learning through the practice of cooperative learning model type Student Teams Achievement Division (STAD) combined with the Project-Based Learning (PJBL) approach in fourth-grade class at SD Muhammadiyah 1 Surakarta. The research uses a descriptive qualitative approach with 23 fourth-grade students as the subject. Data collection is done through observation, interviews, and documentation to gain a deep understanding of the learning process. The implementation of learning is carried out through a project on making "fraction plates" as a concrete medium to understand the concept of equivalent fractions. The results show that practicing STAD-based cooperative learning with PJBL can comprehensively improve the quality of mathematics learning. The improvement is reflected in students' active participation, deeper conceptual understanding, development of teamwork and individual responsibility skills, increased creativity, and the growth of students' motivation and self-confidence in learning mathematics. Therefore, cooperative learning STAD-based on projects is proven to be an effective strategy for meaningful mathematics learning that focuses on developing students' competencies holistically in primary schools.